Está en la página 1de 5

1)

x
2
4
6
0
-2
-4
-6

1 2
f ( x )= x
2

y
2
8
18
0
2
8
18

Dom= R
Calculamos el recorrido

Ran= [0; ∞)

2)

y
3 7,2
2 3,2
1 0,8
0
0
-1 0,8
-2 3,2
-3 7,2

4 2
f ( x )= x
5

x

Dom= R
Calculamos el recorrido

0.√ −4 2 −5 −4 x = y ↔ x 2= y ↔ x=± y 5 4 5 −4 y ≤ 0 ↔ y ≤ 0↔ y ∈ ¿ 5 Ran= 3) ¿ f ( x)3x x y 1.3 -1 3 1. 0.1 5 9 Dom= R Ran = (0.5 5 8 0. 5 5. 1.7 5 3 0 1 0.2 1 3 0. ∞) .

4) x 6 4 2 0 -2 -4 -6 f ( x) 6−x 3−x y 0 -2 4 2 1.6 1. 8 f ( x) = log2(x + 1) y 2. 3) ∪ (3 . 5 1.58 2 1 0 -1. 5 1 0 -1 1.{3} Rang= [0 . ∞) .32 Dom= (-2. ∞) 5) x 1.43 1. 8 1.92 2.81 2.33 Dom= R .

Rang= R 6) f ( x )=sen ( 2 x +2 ) x 3 2 y 0.1 0.01 -3 7 Dom= R Rang= [-1.03 0. 2] .06 1 9 -1 0 -2 0. 1] 7) f ( x )=1+cos ⁡( x−5) Dom= R Rang= [0 .14 0.

∞ ) 4 2) f ( x )=e− x Dom= R Rang= (0. g ( x ) = e 5 5 Dom: (-4.1) 1 x 1 −x f ( x )= e . 1] 4 f ( x )=e− x . 4) Ran: [ 0. ∞ ) Dom: ( −∞ .